2021
DOI: 10.1186/s13567-021-00923-z
|View full text |Cite
|
Sign up to set email alerts
|

Shelter cats host infections with multiple Trypanosoma cruzi discrete typing units in southern Louisiana

Abstract: Trypanosoma cruzi is a zoonotic parasite endemic in the southern US and the Americas, which may frequently infect dogs, but limited information is available about infections in cats. We surveyed a convenience sample of 284 shelter cats from Southern Louisiana to evaluate T. cruzi infection using serological and PCR tests. Parasites from PCR positive cats were also genotyped by PCR and deep sequencing to assess their genetic diversity. We detected a seropositivity rate for T. cruzi of at least 7.3% (17/234), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Maximum likelihood phylogenetic trees were constructed using PHYML as implemented in phylogeny.fr including separate iterations of trees for DTU TcI only, DTUs TcII/TcV/TcVI only and DTU TcIV only. Mini-exon sequences from triatomine vectors, dogs, cats, rodents, non-human primates and humans from North America (Pronovost et al ., 2018 ; Villanueva-Lizama et al ., 2019 ; Herrera et al ., 2019 a ; Dumonteil et al ., 2020 a , 2020 b , 2021 ) were also included for comparison.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Maximum likelihood phylogenetic trees were constructed using PHYML as implemented in phylogeny.fr including separate iterations of trees for DTU TcI only, DTUs TcII/TcV/TcVI only and DTU TcIV only. Mini-exon sequences from triatomine vectors, dogs, cats, rodents, non-human primates and humans from North America (Pronovost et al ., 2018 ; Villanueva-Lizama et al ., 2019 ; Herrera et al ., 2019 a ; Dumonteil et al ., 2020 a , 2020 b , 2021 ) were also included for comparison.…”
Section: Methodsmentioning
confidence: 99%
“…In southern Louisiana, and across the southern United States (US), Trypanosoma cruzi infection exists as an important anthropozoonosis, prevalent in both wildlife and domestically maintained species in this region. Infection has been reported in rodents, dogs, cats, non-human primates and even a domestic llama in the state (Pronovost et al ., 2018 ; Elmayan et al ., 2019 ; Herrera et al ., 2019 a ; Dumonteil et al ., 2021 ; Thompson et al ., 2021 ). Transmission occurs through contact with infected feces of Triatoma sanguisuga insects, the primary vector in the state, though both oral transmission resulting from ingestion of infected insects and congenital transmission have also been suggested to contribute to wildlife infection (Roellig et al ., 2009 b ; Kribs-Zaleta, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 11 triatomine species can transmit T. cruzi in the United States, with Triatoma sanguisuga the most relevant species in the southeastern part of the country [3]. It is responsible for an active zoonotic parasite transmission cycle involving multiple sylvatic and synanthropic mammalian hosts, with frequent spill-over in domestic animals including pet dogs and cats [4][5][6][7], and occasional cases of autochthonous human cases, as seen in Mississippi [8], Tennessee [9] and Louisiana [10].…”
Section: Introductionmentioning
confidence: 99%
“…Only 7.6% of the cats were simultaneously positive to both tests, showing a large discrepancy between these methods [ 123 ]. Recent studies in the US revealed 7.3–11.4% of the cats were seropositive in South Texas [ 12 ] and Louisiana [ 124 ], respectively. Among studies that investigated T. cruzi infections in cats, the highest prevalence was reported in Trinidad and Mercedes, two rural villages in the province of Santiago del Estero, Argentina [ 17 ].…”
Section: Introductionmentioning
confidence: 99%